Labor involvement and productivity in an agribusiness in Sinaloa, Mexico (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2016)
Some authors such as (Shmailan, 2016), Chung-Chieh Lee and Chih-Jen Chen(2013) and (Langfred, 2004) , had explored the relation between labor involvement and work productivity. In this research we enquired this relation in a company from the agri business field in which we used a survey as an instrument in order to obtain the information.We established labor involvement as an independent variable and work productivity as a dependent variable, we used indicators in order to measure their relations. The main findings primarily registered that the indicators related to labor involvement that had more relation with work productivity were task importance and training. With less relation were labor satisfaction and work environment. The study identified that the incentives, tasks autonomy and tasks variety, reflect such a low relation with work productivity. At last, the indicator feedback resulted with null relations with the dependent variable.
Keywords: labor involvement; productivity